Wall Gardening Sebagai Strategi Pemberdayaan Masyarakat Perkotaan Melalui Konsep Urban Farming - Soelaksini, Liliek Dwi; Alif, Trisnani; Widodo, Tirto Wahyu; Muhklisin, Ilham; Arisandi, Dewi Puspa; Nurfadilah, Nurfadilah (P3M Politeknik Negeri Jember, 2025)
Urban communities are generally communities that have homes with limited agricultural land. PKK RW 27 Tegal Boto Lor, Sumbersari District, Jember Regency, East Java has tried to utilize limited land for agricultural activities by planting trees and ornamental plants on the side of the road. Based on this, the Community Service Implementation Team helped provide innovation by introducing the application of the urban farming concept through wall gardening. The method used is through education and soft skill training with the aim of opening the community's insight and knowledge about the innovation of the urban farming concept through wall gardening activities. Based on the activities that have been carried out, there has been an increase in community knowledge with good criteria from 20% (pre-test) to 53.4% ​​(post-test).